Chhaupadi Pratha: Women’s Experiences and Perceptions about Social Suffering - Khadka, Nirajan (Molung Educational Frontier, 2020)
Chhaupadi Pratha, a socio-cultural system, is mostly exercised at the Far Western region of Nepal. The system is linked with biological process of women's menstrual period. Women are kept in small sheds away from home during their menstrual period. Besides difficulties staying in a small hut, they have to suffer from many physical and psychological problems. In that period, they are not allowed to take part in religious ceremonies, family kitchen for nutritious food, and family home for security, and warm. This article attempts to analyze women's experience and perception towards Chhaupadi system. In doing so, it investigates how women are suffering from the Chhaupadi system and its consequences. This ethnographic research employed unstructured in-depth conversations and key informant interviews methods to collect information. This research finds that these women are affected physically and mentally by the practices of Chhaupadi. The practice restricts women's safe live and educational opportunity because they are restricted touching anything during their period. The concept of pollution and purity differentiate the life situation of women which is depended on monthly menstrual bleeding. Menstruating women are believed as polluted that’s why they are forced to live small shed and face various difficulties. Non-menstruating women are believed as a pure. Consequently, their social relationship disturbed by shame and restriction. Living in the Chhaupadi shed brings psychological and physical threats. The discrimination during the periods faced by women is considered as violation of fundamental human rights. Women activists are engaged in campaign against the system.